Peer Helping Programs in the Colleges and Universities of Quebec and Ontario - Lawson, Diane (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper presents the results of a study on peer helping in 19 colleges and universities in Ontario and Quebec. A review of the research associated with peer helping is summarized and the various roles played by peer helpers at the post secondary level are described. An interview questionnaire was designed to gather information about peer programs. Questions focused on goals and rationale, peer selection methods, training, logistics, program monitoring, evaluation, follow-up, difficulties encountered, and marketing strategies. In addition, peer leaders and program co-ordinators were asked about recommendations they would make to prospective peer program developers. General findings and trends are presented.